2020
DOI: 10.1016/j.bios.2020.112316
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-sensitive and high-throughput CRISPR-p owered COVID-19 diagnosis

Abstract: Recent research suggests that SARS-CoV-2-infected individuals can be highly infectious while asymptomatic or pre-symptomatic, and that an infected person may infect 5.6 other individuals on average. This situation highlights the need for rapid, sensitive SARS-CoV-2 diagnostic assays capable of high-throughput operation that can preferably utilize existing equipment to facilitate broad, large-scale screening efforts. We have developed a CRISPR-based assay that can meet all these criteria. This assay utilizes a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
285
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(294 citation statements)
references
References 33 publications
3
285
0
1
Order By: Relevance
“…Direct diagnostic testing to detect active SARS CoV2 infec tions mostly involves reverse transcriptase real time PCR (rtPCR), although different molecular techno logies, such as CRISPR mediated detection or loop mediated isothermal amplification, have also been appl ied [8][9][10][11][12] . Operation and application of these molecu lar tests is in keeping with those for previously developed tests that detect infectious agents 13 .…”
Section: Diagnostic Tests Developed and Their Applicationmentioning
confidence: 99%
“…Direct diagnostic testing to detect active SARS CoV2 infec tions mostly involves reverse transcriptase real time PCR (rtPCR), although different molecular techno logies, such as CRISPR mediated detection or loop mediated isothermal amplification, have also been appl ied [8][9][10][11][12] . Operation and application of these molecu lar tests is in keeping with those for previously developed tests that detect infectious agents 13 .…”
Section: Diagnostic Tests Developed and Their Applicationmentioning
confidence: 99%
“…Therefore, there is still an urgent need for more strategies that can be applied for rapid, accurate and sensitive diagnosis of COVID-19 patients even before an immune response can occur and more importantly for asymptomatic individuals. 14,15 Recent advances in structural biology have revealed that SARS-CoV-2 contains four main structural proteins, including the nucleocapsid (N), spike (S), envelope (E), and membrane (M) proteins. 16 Among them, the N protein is the most abundant, and relatively conserved protein in coronaviruses, which is involved in the transcription and replication of viral RNA.…”
Section: Introductionmentioning
confidence: 99%
“…Although RT-PCR can be used for quantitative analysis and OR-DETECTR cannot, the judgment of negative and positive results between the two platforms was consistent comparing CT and FC values (Figure 2a, 2b, S3, Table S2). 19,20). The amplification of viral nucleic acid is the key to whether it can be specifically detected.…”
Section: Methodsmentioning
confidence: 99%